Urban food systems governance in Africa: Toward a realistic model for transformation - Haysom, Gareth; Battersby, Jane (International Food Policy Research Institute, 2023)
This chapter focuses on African cities and problematizes emerging food system and urban system trends and actions in these cities. The focus on Africa is deliberate. While other areas of the Global South are encountering dramatic urban transitions, Africa’s dramatic demographic shift raises important political economy challenges. Specifically, Africa’s median age is only 19 years, and 41 percent of the population is 14 years of age or younger; the continent will become increasingly younger over the next 30 years. Given past demographic trends and rates of urbanization, the majority of those born in Africa will be born in cities. Ensuring that the urban food system guarantees the attainment of optimal developmental and health outcomes is therefore essential, both to ensure the youth dividend and for society at large. The rapid transformation of both Africa’s cities and food systems demands new and novel forms of governance. Until recently, Africanists have largely ignored, or were openly hostile to, almost all aspects of a wider urban agenda, focusing instead on issues such as the peasantry, agriculture, natural resource use or national sovereignty. Food insecurity therefore has been framed as predominantly experienced in rural areas, and to be addressed by increased agricultural production, and food and cities are seldom seen as being spatially connected and mutually dependent on one another in African food system discourses. Beyond being the recipient of food produced in rural areas, urban areas have largely been neglected in food security policy and governance.